2018
DOI: 10.1177/1750481318766922
|View full text |Cite
|
Sign up to set email alerts
|

Exclusionary visual depiction of disabled persons in Malaysian news photographs

Abstract: Disability has been perceived as a social conditioning phenomenon and a sign system marking the body and mind. Accordingly, photographs of disability could shape our cultural perceptions about disability and disabled persons. In response to this position, we engage in a critical semiotic inquiry into press photographs of disability ( N = 1002) from The Star, a Malaysian mainstream English newspaper. We adapted Van Leeuwen’s (2008) social and visual actor networks to understand the visual techniques employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Within the Malaysian context, two studies have focused on general media depictions of disabled persons and how they were under-represented or represented prejudicially (e.g., Ang & Yeo, 2018; Baskaran, 2004). The focus of these studies were on verbal (Baskaran, 2004) and visual depictions (Ang & Yeo, 2018). In another study, article content analysis was used as the main analytical tool.…”
Section: Disability Sport and Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Malaysian context, two studies have focused on general media depictions of disabled persons and how they were under-represented or represented prejudicially (e.g., Ang & Yeo, 2018; Baskaran, 2004). The focus of these studies were on verbal (Baskaran, 2004) and visual depictions (Ang & Yeo, 2018). In another study, article content analysis was used as the main analytical tool.…”
Section: Disability Sport and Mediamentioning
confidence: 99%
“…For example, a study about Malaysian newspaper coverage of the 2012 London Paralympic Games showed that most of the articles contained positive references to athletes and featured more male than female athletes (Cheong et al, 2016). Furthermore, research using a linguistics framework had been used to examine disability and disabled persons of non-sporting nature in Malaysia (Ang & Knox, 2020; Ang & Yeo, 2018). Despite these existing studies, there is still limited research about disability representation in the media in Malaysia.…”
Section: Disability Sport and Mediamentioning
confidence: 99%
“…In the broader context, images of dementia have also been included in research on photographs of disability. Photographs of disability carry social connotations and are often marked with signs of disability (Ang & Knox, 2020; Ang & Yeo, 2018; Garland-Thomson, 2002). These signs also interpret disabilities as anatomical, neurological and physical deficits requiring potential repair (Candlin & Crichton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The same seems to be true for Malaysia. Ang and Yeo stated that: "Disabled persons in Malaysia are deprived of rights due to public apathy and prejudice, as well as failure of society and the authority to provide the necessary resources and infrastructure for them to function independently" [5].…”
Section: Introductionmentioning
confidence: 99%